Localizing Decent Work for Domestic Workers - Co, Justine (Archīum Ateneo, 2021)
In 2013, International Labor Organization (ILO) Convention 189 or the Convention Concerning Decent Work for Domestic Workers was ratified. The institutionalization of this norm at the transnational level is one of the major victories of a global movement consisting of domestic workers groups, labor unions, and human rights advocates. In the same year that ILO C189 was ratified, the country passed Batas Kasambahay, a law recognizing the rights of domestic workers. My thesis examines the role of transnational and local actors in localizing decent work for domestic workers within the Philippines. It adopts a qualitative method of inquiry where key informant interviews with members of United Domestic Workers of the Philippines, the International Domestic Workers Federation, and the ILO Technical Working Group on Domestic Work were conducted. Thematic analysis was used to analyze the qualitative information. This study argues that the decent work for domestic workers norm has yet to be internalized despite its institutionalization through Batas Kasambahay in the Philippines. Barriers to internalization include the “divide” between migrant and local domestic work issues, a young domestic workers movement, and cultural attitudes toward domestic work. Local actors are in the process of internalizing decent work for domestic workers by strengthening their transnational and local networks and organizing local domestic workers.